DAMPAK SOSIAL EKONOMI MELALUI PEMBERDAYAAN MASYARAKAT (STUDI BUDIDAYA SARANG BURUNG WALET DI KECAMATAN BELOPA KABUPATEN LUWU) - Fauzy AR, Ismail; Kaharuddin; Ismail, Lukman (Universitas Bina Taruna Gorontalo, 2025)
This study aims to examine the contribution of the swallow's nest cultivation business to increasing income and community welfare in Belopa District, Luwu Regency. The research method used is a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation of ten informants of swallow business actors, community leaders and communities close to the swallow's nest cultivation location. The results of the study indicate that swallow's nest cultivation has a significant economic impact, including increasing family income, creating new jobs, increasing purchasing power, and improving the quality of life of the community. In addition to the economic aspect, this study also found social impacts such as the formation of a solidarity network between swallow's nest cultivation business actors and the emergence of a family-based economic community. However, this business also faces social obstacles in the form of inequality in economic access, potential social conflict, and environmental impacts due to noise and waste from swallow houses. Based on these findings, the researcher recommends policy support from the local government in the form of zoning regulations, technical training, capital assistance, and the formation of swallow farmer cooperatives to create sustainable and inclusive businesses